The 7th international continuous scientific-practical conference: “Worldfor a Child: Education Realities and Prospects” - Autukevičienė, Birutė; Monkevičienė, Ona (Pedagogika, 2018)
On 19th of April, 2018 the 7th continuous scientific-practical conference: “World for a Child: Education Realities and Prospects” was held in Lithuanian University of Educational Sciences where researchers and practitioners analysed the changes of the conception of child hood in historical and cultural contexts, innovative aspects of curriculum content and didactics, digital technologies enriching the educational process, new media, STEAM activities and the education of a new generation of teachers.